Urinary Angiogenin Reflects the Magnitude of Kidney Injury at the Infrahistologic Level - Tavernier, Quentin (J Am Soc Nephrol, 2017)
The ribonuclease angiogenin is a component of the mammalian stress response that is secreted by renal epithelial cells on activation of the inositol–requiring enzyme 1α (IRE1α)–active spliced X–box binding protein 1 (sXBP1) axis and instrumental to the adaptation to AKI associated with endoplasmic reticulum stress. To determine whether the amount of angiogenin in urine of individuals with a kidney injury reflects the magnitude of the lesions and provides information on the risk of organ failure, we examined individuals referred for a kidney injury and determined the biochemical characteristics of urinary angiogenin and its diagnostic and prognostic values. Urinary angiogenin did not correlate with the urinary concentrations of high molecular weight proteins and correlated only weakly with low molecular weight proteins, suggestive of tubular production. In a cohort of 242 kidney transplant recipients with acute allograft dysfunction, higher urinary angiogenin concentrations at the time of the biopsy associated with worse renal function and higher proteinuria but did not correlate with histologic lesions as defined in the Banff classification. Kidney transplant recipients with urinary angiogenin amounts in the highest 50% had a risk of graft failure 3.59 times as high (95% confidence interval, 1.12 to 15.94) as that of patients with amounts in the lowest 50%. Finally, the amount of urinary angiogenin reflected the activity of the IRE1α-XBP1 axis in allografts. Our approach identified urinary angiogenin as a noninvasive indicator of the extent of tissue damage, independent of the histologic lesions, and a risk predictor of kidney allograft failure.